Analisis Peran Teknologi Digital Dalam Memudahkan Nasabah Bertransaksi Pada Saat Terjadi Pandemi Covid-19 (Studi Kasus Bank Sumut Syariah Capem Hamparan Perak) - Sri Rezeki; Nurbaiti Nurbaiti; Nurwani Nurwani (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Digital technology is a type of technology in which computer systems and automated systems usually replace a lot of human labor in the process. This study aims to determine the role of digital technology in Bank Sumut Syariah Hamparan Perak Sub-Branch to make it easier for customers to make transactions during the Covid-19 pandemic. This study uses a descriptive qualitative approach. Techniques and data collection using structured interviews and using secondary data obtained from PT. SOP data. Bank Sumut Syariah Sub-branch of Overlay Silver and so on. The results of the first research on the role of digital technology provide convenience in using mobile banking during the Covid-19 pandemic which has a good impact related to increasing the number of customers. The results of the second study are constraints on the role of digital technology in making it easier for customers to make transactions during the Covid-19 pandemic regarding the limited internet or not yet entering rural areas. Suggestions and input for Bank Sumut Syariah Capem Hamparan Perak can improve the network by using wireless mobile banking which is prepared as early as possible, where if there is a network failure, the convenience of customer transactions will not be disturbed at all.